COMPLEMENTARY AND ALTERNATIVE MEDICINE USAGE IN CANCER PATIENTS IN SOUTHEAST OF TURKEY - Kucukoner, Mehmet; Bilge, Zulfikar; Isikdogan, Abdurrahman; Kaplan, Muhammed Ali; Inal, Ali; Urakci, Zuhat (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The aim of this study was to investigate the frequency of complementary and alternative medicine (CAM) methods and clinical characteristics in cancer patients in southeast of Turkey. A total of 324 patients (173 female) were enrolled to this study. Questionnaire was applied to all patients individually for approximately 15 minutes by a doctor. At least one CAM method was used by 62% (n=201) of the patients. 82.5% (n=166) of patients treated with CAM were using at least one herbal species. Likewise, 40.9% (68/166) of these patients were using herbal mixtures and 39.8% (66/166) of them were using single herbal as nettle (Urtica dioica) or its seed, 19.3 % (32/166) of them were using other herbals. CAM methods were preferred more frequently by the patients with metastatic stage (p=0.005), receiving palliative treatment (p<0.001), chemotherapy (p=0.020), in between 40-60 ages patient groups (p=0.002), and when duration of disease was lengthened (p=0.002). CAM use among cancer patients is quite common. Presence of metastatic cancer at diagnosis, receiving chemotherapy and palliative treatment and long disease duration were found as main associated factors for CAM usage.